SIRT2-dependent DKK1 deacetylation aggravates polycystic ovary syndrome by targeting the TGF-β1/Smad3 signaling pathway - Lan Chen; Caixia Kong (Taylor & Francis Group, 2024)
Background Polycystic ovarian syndrome (PCOS) is a prevalent metabolic and endocrine condition in females of reproductive age. This work was to discover the underlying role of Dickkopf 1 (DKK1) and its putative regulating mechanism in P COS.Methods Mice recieved dehydroepiandrosterone (DHEA) injection to establish the in vivo P COS model.Hematoxylin and eosin (H&E) staining was performed for histological analysis. RT-qP CR and Western blotting were used to detect gene and protein expression. CCK-8 and flow cytometry assays were applied to detect cell viability and apoptosis. Co-immunoprecipitation (Co-IP) and immunoprecipitation (IP) were applied to assess association between DKK1 and SIRT2.Results In this work, DKK1 is downregulated in P COS rats. It was revealed that DKK1 knockdown induced apoptosis and suppressed proliferation in KGN cells, whereas DKK1 overexpression had exactly the opposite effects. In addition, DKK1 deactivates the T GF-β1/SMad3 signaling pathway, thereby controlling KGN cell proliferation and apoptosis. Besides, SIRT2 inhibition reversed the impact of DKK1 overexpression on KGN cell proliferation and apoptosis. Furthermore, SIRT2 downregulated DKK1 expression by deacetylating DKK1 in KGN cells.Discussion Altogether, we concluded that SIRT2-induced deacetylation of DKK1 triggers T GF-β1/Smad3 hyperactivation, thereby inhibiting proliferation and promoting apoptosis of KGN cells. The above results indicated that DKK1 might function as a latent target for P COS treatment.